Strategic sale versus public offer: dispelling myths - Mohan, T.T. Ram (2003)
The focus in India's privatisation efforts has shifted from disinvestment, the sale of minority shares to the public, to strategic sale where a controlling stake is sold to a private buyer. It is contended that strategic sale, by transferring control from government to a private owner, is best suited to the objective of improved efficiency. Because a process of bidding subject to a reserve price is involved, it will also help meet the objective of maximising government revenues through privatisation. This paper reviews these claims drawing on the findings of auction theory and the empirical evidence on methods of sale in privatisation worldwide. It also addresses popular misconceptions about the benefits of strategic sale. The auction literature suggests that strategic sale using the first-priced sealed-bid method currently employed cannot always be counted upon to maximise efficiency and revenues. The empirical evidence shows that share issue privatisation, the sale of government shares through a public offer, has been the preferred method of sale in privatisation carried out elsewhere. - Reproduced.
Keywords: Privatization